Ankuri Technology for Seed Germination and Seedling Emergence of Rice in Cold Environment - Ansari, Tahmid Hossain; Ahmed, Montasir (Bangladesh Agronomy Journal, 2017)
Rice seed germination as well as seedling emergence in cold environment is a challenge for successful rice cultivation during dry (Boro) season in northern Bangladesh Experiments were conducted in two consecutive Boro seasons in Rajshahi to develop techniques for improving germination and seedling emergence under cold conditions.. Seeds of rice var. BRRI dhan29 and BRRI dhan50 were germinated following the traditional Zag-method and separately in a frame covered with air tight heat insulating plastic tripal (called Ankuri- germinator). Then vapor therapy was given inside Ankuri and maintained 25-350C with high humidity. External and internal temperatures of Ankuri were recorded. Seed germination was checked at 12 h interval. In another experiment, germinated seeds of BRRI dhan29 were sown on soil in trays followed by light irrigation. One set of trays was placed in Ankuri. Another two sets of trays were placed in the field with polythene covered and uncovered. Similar experiment using non-germinated dry seed was also conducted. Vapor therapy was applied in Ankuri only in and trays were checked regularly to observe the plumule and radicle growth. The germination rate (%) of the tested varieties in Ankuri ranged from 82-96% which was 64-92% in Zag-method. High variation of germination in Zag-method was due to improper temperature and humidity during the Zag period. Seed germination was faster in Ankuri which was observed within 2.5 days. This was also 2.5 days earlier in comparison with the Zag-method. Soaking period ranged 22-24 h outside in cold water/weather. But 18 h soaking in Ankuri resulted good germination. Irrespective of varieties, the growth was 5.4 and 1.7 times more respectively for plumule and radicle in Ankuri than Zag-method. Seedling emergence was 2-3 days earlier in both dry and soaked/germinated seeds sown in trays of Ankuri than the outside polythene covered trays. Seedling emergence failed in open-trays. Average air temperature from 18:00-9:00 was cooler (150C) than 9:00-18:00 period (150C). Ankuri maintained 25-350C and high humidity which favored seed germination and seedling growth. Therefore, Ankuri could be an effective seed germination technique with faster germination, radicle and plumule growth. Bangladesh Agron. J. 2016 19(2): 115-123